Itch : the explosive adventures of an element hunter - Mayo, Simon. 1958- . (New York, NY : Splinter, 2012)
When fourteen-year-old Itchingham "Itch" Lofte discovers a new radioactive element, he must use all of his wits and scientific knowledge to stop a top-secret government agency, his greedy teacher, and an evil corporation from getting hold of it.
Previously published in Great Britain by Random House Children's Books, 2012.
Includes an excerpt from Itch rocks (p. [419]-425).
Keywords: Chemical elements -- Juvenile fiction; Adventure stories; Cornwall (England : County) -- Juvenile fiction; England -- Juvenile fiction